The Impact of Renewable Energy Consumption on Economic Growth in Seven ASEAN Countries - Mulyani Mulyani; Asep Munir Hidayat; Billy Tejaarief; Kenedi Kenedi; Anti Wulan Agustini (Transpublika Publisher, 2025)
Renewable energy has become a global priority to reduce fossil fuel dependence and environmental impact. Seven ASEAN countries (Indonesia, Malaysia, Thailand, Vietnam, Philippines, Singapore, Cambodia) face significant challenges in maintaining energy stability while promoting sustainable development. This study analyzes the direct effects of Renewable Energy Consumption, Electricity Consumption, and Trade on Economic Growth from 2014 to 2023 in seven ASEAN countries. Secondary data analysis using a quantitative approach was employed. The sample consisted of seven countries selected through purposive sampling. Panel data analysis was conducted using Eviews10 program. The F-statistic value of 568.6365 exceeded the F-table value of 3.13 at 95% confidence level, rejecting the null hypothesis. Collectively, Renewable Energy Consumption, Electricity Consumption, and Trade significantly influence Economic Growth. Country-specific analysis revealed that renewable energy consumption affects economic growth across all countries, electricity consumption significantly influences growth in Cambodia and Vietnam, while trade contributes to economic growth in Malaysia and Vietnam. The findings demonstrate that energy transition and regional economic integration play crucial roles in supporting long-term economic growth in the ASEAN region. Each country exhibits varying responses to different energy and trade factors, indicating the need for tailored sustainable development approaches.